PENGELOLAAN MODAL KERJA PADA KOPERASI SIMPAN PINJAM WARGA MAKMUR UNIT MARISA KABUPATEN POHUWATO - Tamsir Tamsir (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2016)
The purpose of this study is to analyze the extent to which the management of working capital in Warga Makmur Credit Unions Marisa Unit in terms of liquidity ratios, activity and profitability rasioa. Based on the analysis and discussion on Warga Makmur Marisa Unit were reviewed based on the figures resulting ratio showed a very good or liquid in the Current Ratio analysis is the number that corresponds to the standard (134.23% in 2012, 140.29% in 2013 and 162.14% in 2014), while the Quick ratio analysis showed very good results, as compared to the ratio pda years 2012 to 2014, the average value of 114.99% platinum or are in the standard (100% - 125 %), working capital management in credit unions Makmur Residents Unit Marisa terms of ratio analysis activity (Turnover of receivables) showed good results (<48 months), which is a sequential basis; 30 months, 11 months and 12 months. Meanwhile, working capital turnover ratio shows the results quite efficient (1 times - 0 time), ie consecutive secar was 0.72 times, 0.70 times and 0.59 times. Management of working capital in the savings and loan cooperatives Makmur Residents Unit Marisa terms of profitability ratios in the category fairly efficient. The profitability ratio shows that the cooperative Citizens Makmur rentabel in generating maximum SHU. It is seen from the figures produced are suitable ratios primarily to the standards set, which is an average of 9.44% and in the category very efficient (9% - 10%). It is seen from the figures produced are suitable ratios primarily to the standards set, which is the average in the category of good, fairly good, fairly efficient and streamlined.